The abundance of parasitic nematodes Halicephalobus species (Nematoda: Rhabditida) invading humans and animals in national parks of Vietnam - Tho Son, Le; Mai Huong, Bui Thi; Bich Hong, Ha; Thu, Nguyen Thi (Vietnam Journal of Biotechnology, 2023)
Halicephalobus nematodes are parasites in horses, ruminants, and humans. They with the most demonstrated H. gingivalis infect the hosts and cause granulomas to fatalities. Anthelmintic treatments are not effective in many cases, so precautions against Halicephalobus infection based on the understanding of life history may help. So far, ten species have been globally identified. We isolated many wild-type Halicephalobus sp. strains in vegetation samples collected from two national parks (Cat Tien and Cuc Phuong National Parks) in Vietnam and cultured them on bacteria. Thus, Halicephalobus nematodes could live in the wild and feed on bacteria. In previous studies, horses were predominantly found to be hosts of Halicephalobus sp. nematodes, but in this study they are not presented in the parks, suggesting that other wild animals such as ruminants in the parks should be their hosts. In addition, we analyzed the 18S rDNA sequences of the isolated nematodes and found that they are likely divergent between the two ecological systems, suggesting the two nematode communities have evolved differently.